Exploring the relationship between willingness to communicate and cultural capital in a language learning context - a qualitative investigation - Trinder, Magdalena (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
The qualitative study is intended to determine if there is a potential relationship between willingness to communicate and cultural capital in young learners of English and whether it may be possible to assess levels of cultural capital and cultural participation in a quantitative fashion, which would then open the way for a broader range of studies that would allow for regressive analysis of the relationship between cultural capital and a broad range of individual differences to determine the extent to which this may be a key factor in language acquisition and learning. The qualitative investigation was conducted on five participants who were willing to give interviews during a language camp in the UK in the summer of 2022. All five of the participants scored highly on a WTC assessment scale and also showed confidence in communicating in a non-classroom environment. The tentative findings of the study would appear to indicate that there is a firm basis for further research on a quantitative scale in order to validate the basic hypothesis.
Keywords: willingness to communicate; cultural capital; cultural participation; individual learner differences; second language acquisition